Simulation of Sea Waves and Investigation of Extractable Energy from Waves in Makran Coastal Zone by Using SWAN Model - Mona Kashi Zonozi; Behzad Layeghi; Abbas Ranjbar; Sahar Tajkbakhsh; Mehdi Rahnama (Nīvār)
In recent years, the need for energy in the world has increased. Due to climate change and its problems and the increasing global need for energy, the desire to use fossil energy has decreased and the development of new energy has become one of the most important issues of the day. In this research, one of the new types of energy, called wind wave energy, has been investigated. In this research, the Swan model (SWAN: Simulating Waves Nearshore) was used to simulate the characteristics of the waves (Significant wave height, wave direction and wave period) were predicted in a period of 6 years. The output of the WRF model was used to generate the wind field of the SWAN model input. After simulating the waves, the Chabahar buoy and Era5 data were used to verify the wave characteristics, including the height of the wave index (Hs) and the period of wave repetition (Ts). Then, the amount of energy that can be extracted in Makran beaches was calculated. The results of the six-year averaging showed that the highest wave power can be obtained in the summer season in the areas near the Indian Ocean, which was estimated about 7.84 W/m.